How do informal social networks impact on labor earnings in Turkey? - Yanık İlhan, Bengi; Bayar, Ayşe Aylin; GÜMÜŞOĞLU, NEBİLE KORUCU (My University, 2019)
The informal social networks are one of the prominent factors in the labor market decisions both for the supply and demand side. Particularly, in developing countries, like Turkey, these informal networks have an influence on the labor market. However, even the existence of this issue, the impact of informal social networks has not been argued sufficiently for the Turkish case. In this respect, this study advances existing researches, by implementing the quantile regression method to reveal the impact of the informal social networks. The quantile regression analysis reveals the impacts of the different quantiles of wages. The Household Labor Force Survey (HLFS) is utilized for 2004-2016 period. The findings indicate that being recruited by social contacts has negative impact on wage levels and in consequence, aggregate productivity is decreased from low quality of labor force and the low return to the firm.
Keywords: Informal Networks; Quantile Regression; Employment; Turkey; Gayri Resmi Ağlar; Kuantil Regresyon; İstihdam; Türkiye